2020
DOI: 10.12659/msm.925187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Atlantoaxial Dislocation Combined with Osteoporosis Using Posterior Atlantoaxial Rod, Screw Fixation, and Posterior Interfacet Fusion: A Retrospective Study of 21 Cases

Abstract: Background Surgical procedures on atlantoaxial dislocation combined with osteoporosis remain controversial. This study was established to assess the mid-term clinical outcomes of atlantoaxial dislocation combined with osteoporosis using posterior atlantoaxial rod, screw fixation and posterior interfacet fusion. Material/Methods From January 2017 to January 2020, 21 patients (4 males and 17 females) with coexisting atlantoaxial dislocation and osteoporosis who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The removal of cartilage and roughing up of the atlantoaxial joints bilaterally provide an ideal environment for postoperative fusion. Besides, the contact area of the bone‐graft bed in the atlantoaxial joints is large enough for the placement of bone autograft, which make it more conducive to the fusion of the autograft 5,29,30 . Additionally, the bone autograft acts as a stimulus for living bone growth and maintains structural strength immediately.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The removal of cartilage and roughing up of the atlantoaxial joints bilaterally provide an ideal environment for postoperative fusion. Besides, the contact area of the bone‐graft bed in the atlantoaxial joints is large enough for the placement of bone autograft, which make it more conducive to the fusion of the autograft 5,29,30 . Additionally, the bone autograft acts as a stimulus for living bone growth and maintains structural strength immediately.…”
Section: Discussionmentioning
confidence: 99%
“…However, bone graft fusion is key to achieving long‐term maintenance of stability. 1 , 2 Regarding fusion, although several studies have shown that the rate of bone graft fusion with internal fixation was higher, 1 , 2 , 5 some patients still experience unsatisfactory bone graft healing and postoperative complications resulting from postoperative nonunion of bone grafts. 19 It has been reported that the rates of instrumentation failure after nonunion were about 6.7% during atlantoaxial fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations